Language Awareness in the Second and Foreign Language Grammar Classroom - Arshad Abd. Samad (Universitas Negeri Padang, 2014)
In the many decades since Applied Linguistics became a formalized and popular academic discipline, we have been introduced to several inter related terminology in language pedagogy that are used to help explain the process of becoming proficient in a second language. These terms include language acquisition, intake, the developing interlanguage system, and more recently, language awareness. From the perspective of language teachers, these terms and the concepts they describe formally state desirable goals and point in the direction to which we want to bring our students but do not provide explicit information on how we can do so. Although language awareness may best be described as an educational movement in its initial stage, it has now taken on varying perspectives that affect almost all aspects of language use and consequently has clear implications on how language should be taught in classrooms. This paper will begin by briefly examining the concept of language awareness and its scope. It will then discuss some possible ways how language awareness can occur in an educational context and finally, drawing upon work conducting by earlier practitioners, especially Batstone (1995), the paper will propose a format for incorporating language awareness into the second and foreign language grammar classroom.